Espiritualidade litúrgica em “tempos líquidos” - Santos, Diego Willian dos (2019)
It is undeniable that cultural changes and technological scientific development impact people’s lives in the way they perceive relationships, friendships, or even how they interact with objects and worldly goods. Such change also creates a transformation on the ecclesiastical sphere, altering one’s relationship with God and, consequently, with belief and spirituality. Therefore, the present research aimed for the analysis of the current spirituality impact borne by the post Vatican II council liturgy and its partakers. The established reflection here was based on the spirit imbued within the Conciliar Sacrosanctum Concilium document, merged with sociologist Zygmunt Bauman’s thought process, which defined our society as liquid. Thus, this essay is going to study how the consumerist and marketing-oriented mentality has been overrunning the ecclesiastical environment, exhibiting an erroneous comprehension of spirituality and, as a result, of the relationship with God and further catholic Christianity practitioners. In addition, impacts that such mentality may create on the liturgical spirituality experience will be analyzed, as well as the concrete aspects that are presented as goals by the liturgy, in order for people who are permeated by the culture of modern liquid society not to succumb to numerous ephemeral and fleeting invitations, which do not lead to the real exercise of catholic Christian spirituality. Simultaneously, this research reflects about a possible dialogue with the modern world, with the purpose of rescuing the liturgical spirituality, which builds a solid path to follow Jesus Christ